EFEKTIFITAS PERAWATAN PAYUDARA IBU POST PARTUM DENGAN PRODUKSI ASI DI PMB MARYATI, Amd.Keb KARAWANG BEKASI - Junita, Friska (Jurnal Ayurveda Medistra, 2023)
Background: Breast milk is the best nutritional liquid and has many important nutrients to support the baby's growth. Based on Riskesdas 2021, 52.5% of the 2.3 million babies do not receive exclusive breastfeeding. One of the factors causing babies not to get exclusive breastfeeding, such as flat or immersed nipples, sore nipples, swollen breasts, mastitis, improper breastfeeding position. Various efforts can be made to facilitate breast milk, one of which is breast care. Objective: To find out the effectiveness of breast care for post partum mothers with smooth breastfeeding at PMB Maryati Amd.Keb in 2023. Method: Implemented with a quasi-experimental design using a one group pretest and posttest design. with a total sample of 13 people. In the pre-test, the smoothness of the milk before breast care was seen, and in the post-test, the smoothness of the milk was evaluated after the mother had received breast care for 7 days, carried out 2x a day (morning and evening). Results: Characteristics of respondents based on average age were at the age of 20-30 years 61.5%, High School Education 69.2%, Parity 3-4 children 46.2%, Normal delivery 92.3%, BBL> 2500gr namely 92 .3%. For a comparison before and after further breast care shows that the value of sig(2tailed) t paired is 0.000. Conclusion: There is an effect of breast care on post partum mothers with the smoothness of breastfeeding at PMB Maryati Amd.Keb in 2023.